Use of Transcranial Direct Stimulation in the Treatment of Negative Symptoms of Schizophrenia. (January 2018) - Pontillo, Maria; Costanzo, Floriana; Menghini, Deny; Averna, Roberto; Santonastaso, Ornella; Tata, Maria Cristina; Vicari, Stefano
Schizophrenia is a debilitating disease that affects approximately 1% of the population. Negative symptoms are among the major determinants of the functional impairment and a significant proportion of patients with negative symptoms will continue to experience these symptoms despite antipsychotic medications. There are promising results in the application of brain stimulation, particularly transcranial direct current stimulation (tDCS), for the reduction of negative symptoms of schizophrenia. However, findings are still controversial. This is a selective review of the literature published between 2011 and 2017 on use of tDCS in treatment of negative symptoms of schizophrenia. We included only randomized controlled trials where schizophrenia and negative symptoms were assessed using any psychometrically validated scale (eg, Positive and Negative Symptoms Scale or Scale for the Assessment of Negative Symptoms). Studies of participants with neurological conditions were excluded, as were those that did not report any symptom outcome variables. Only 5 studies are included. Three studies showed a decrease of negative symptoms. The other studies did not show any therapeutic effects of tDCS in the severity of positive and negative symptoms compared to controls. Our findings suggest that negative symptoms in schizophrenia can be treated with tDCS over the dorsolateral prefrontal cortex, but results are affected by several factors, such as the electrode montage, the concomitant medication, the homogeneity of the sample, the intensity of the tDCS treatment. Further randomized, double-blinded, sham-controlled studies in large samples are still needed to establish the effectiveness of the tDCS in the treatment of negative symptoms in schizophrenia, but there is the potential for tDCS to become a useful complementary treatment option in this population.